2007
DOI: 10.1038/sj.onc.1210836
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression signature of human sarcomas

Abstract: MicroRNAs (miRNAs) are B22 nucleotide-long noncoding RNAs involved in several biological processes including development, differentiation and proliferation. Recent studies suggest that knowledge of miRNA expression patterns in cancer may have substantial value for diagnostic and prognostic determinations as well as for eventual therapeutic intervention. We performed comprehensive analysis of miRNA expression profiles of 27 sarcomas, 5 normal smooth muscle and 2 normal skeletal muscle tissues using microarray t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
188
3
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(211 citation statements)
references
References 29 publications
(29 reference statements)
14
188
3
6
Order By: Relevance
“…Of note, dysregulation of miR-16, miR-195 and miR-497 have also been found in a range of other cancers, including chronic lymphocytic leukaemia, prostate, pancreas, cervical carcinomas together with sarcomas and benign uterine leiomyomata (Table 4). 12,[53][54][55][56][57][58][59][60][61][62][63] Little is known about the mechanisms of micro-RNA deregulation in neoplastic tissue. MicroRNA genes are commonly located at minimal regions of amplification, loss of heterozygosity and breakpoint regions, suggesting that abnormal microRNA profiles can be caused by somatic gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, dysregulation of miR-16, miR-195 and miR-497 have also been found in a range of other cancers, including chronic lymphocytic leukaemia, prostate, pancreas, cervical carcinomas together with sarcomas and benign uterine leiomyomata (Table 4). 12,[53][54][55][56][57][58][59][60][61][62][63] Little is known about the mechanisms of micro-RNA deregulation in neoplastic tissue. MicroRNA genes are commonly located at minimal regions of amplification, loss of heterozygosity and breakpoint regions, suggesting that abnormal microRNA profiles can be caused by somatic gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the relevance of this finding, we compared our findings with other published works on miRNA expression profile in rhabdomyosarcoma and compiled expression data for miR-1, miR-133a, miR-133b, and miR-206 from ten studies that compared rhabdomyosarcoma with normal skeletal muscle (Supplementary Table 2). [9][10][11][12][13][24][25][26][27][28] The prior studies showed underexpression of miR-1 and miR-133a (if examined) in all nine studies and variable expression of miR-133b and miR-206 across the comparisons of rhabdomyosarcoma to normal skeletal muscle. The underexpression of the myomiRs miR-1, miR-133a, and miR-206 in well-differentiated liposarcoma was validated using qRT-PCR (Figures 2b and d).…”
Section: Qrt-pcr Analysismentioning
confidence: 99%
“…For example, we and others found that the tumor suppressor miR-29 was found to be downregulated in rhabdomyosarcoma. 9,10 Results identified a regulatory circuit involving miR-29, NF-κB, and YY1 that appears to be dysregulated in rhabdomyosarcoma and might contribute to the dedifferentiation phenotype of these tumors. 9 Re-expression of miR-29 in xenograft tumors and rhabdomyosarcoma cell lines led to inhibition of tumor proliferation as well as stimulation of myogenic differentiation.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] However, there is no comprehensive expression analysis that catalogs miRNA expression patterns in the wide variety of existing sarcoma types with sufficient sample size to carry statistical power. In our earlier studies, we have reported preliminary analysis of miRNA expression levels in a small series of sarcomas 14 as well as in colon cancer. 15 Exhaustive analysis of miRNA expression patterns in sarcomas will accelerate the identification and development of novel miRNA-based biomarkers for these tumors.…”
mentioning
confidence: 99%